2008
DOI: 10.1186/1756-0500-1-64
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae early response genes to human lung epithelial cells

Abstract: Background: Streptococcus pneumoniae infection starts from colonization of the host respiratory tract where interaction with host respiratory tract epithelial cells occurs. To investigate pneumococcal genes that are involved in the early stage of interaction with host epithelial cells, transcriptional responses of an encapsulated pathogenic pneumococcal strain TIGR4 upon exposure to human lung epithelial cells A549 for 0.5 h and 1 h time periods were investigated by using TIGR (JCVI) microarray technology. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
(29 reference statements)
1
23
0
Order By: Relevance
“…We were able to demonstrate a difference in biofilm production after growth on human airway cells, which has been shown to induce nanA expression (27,39,46) and reduce capsule production (16). By selecting for organisms on human airway cells, we apparently mimicked a likely in vivo process in which encapsulated organisms that are able to avoid mucus entrapment and clearance gradually produce less capsule to facilitate epithelial attachment (20).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We were able to demonstrate a difference in biofilm production after growth on human airway cells, which has been shown to induce nanA expression (27,39,46) and reduce capsule production (16). By selecting for organisms on human airway cells, we apparently mimicked a likely in vivo process in which encapsulated organisms that are able to avoid mucus entrapment and clearance gradually produce less capsule to facilitate epithelial attachment (20).…”
Section: Discussionmentioning
confidence: 97%
“…Streptococcus pneumoniae produces at least three distinct neuraminidases (41); NanA is the neuraminidase that is most active and most highly expressed at the transcriptional level (5,31), and it is conserved in all strains (21,24,41). Production of NanA can be detected in vivo, and its expression is upregulated upon interaction with host cells (27,39,46,58). The pneumococcal neuraminidase modifies host glycoconjugates, including immune defense proteins (22,23), and exposes potential binding receptors (3,26,28,54,55).…”
mentioning
confidence: 99%
“…An msmK mutant was significantly reduced in colonization when competed against its parent strain, suggesting that transport of at least one of the carbohydrate substrates is important during colonization. The exact contribution of each of the six transporters is currently unknown; however, previous data suggest that individual transporters vary in their contributions to both colonization and pathogenesis (4,11,16,23,29,37). While we did not assess the contribution of msmK to pathogenesis here, during the revision of the manuscript Tyx et al demonstrated a role for this gene in raffinose transport and pneumococcal pneumonia (40).…”
Section: Discussionmentioning
confidence: 99%
“…NanA is required for pneumococcal growth on mucins (sialylated glycoproteins abundantly found in the respiratory tract) [30] and its expression is upregulated in the presence of lung cells [31]. By deglycosylating human serum components, NanA can interfere with C3 deposition on the pneumococcal surface and reduce opsonophagocytosis by human neutrophils [32].…”
Section: Introductionmentioning
confidence: 99%